2021
DOI: 10.3390/ph14090906
|View full text |Cite
|
Sign up to set email alerts
|

Semaphorin 3A—Glycosaminoglycans Interaction as Therapeutic Target for Axonal Regeneration

Abstract: Semaphorin 3A (Sema3A) is a cell-secreted protein that participates in the axonal guidance pathways. Sema3A acts as a canonical repulsive axon guidance molecule, inhibiting CNS regenerative axonal growth and propagation. Therefore, interfering with Sema3A signaling is proposed as a therapeutic target for achieving functional recovery after CNS injuries. It has been shown that Sema3A adheres to the proteoglycan component of the extracellular matrix (ECM) and selectively binds to heparin and chondroitin sulfate-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 106 publications
0
3
0
Order By: Relevance
“… 76 Studies show that semaphorin-3a (Sema3a)-induced axonal growth cone collapse depends on HS3ST, indicating that activities of the semaphorin family rely on HS modifications. 77 , 78 , 79 TPGs of alopecia mainly cluster into two pathways termed the “Wnt signaling pathway” and the “Hippo signaling pathway” ( Figure 4 L). A previous study indicated that Wnt/β-catenin and Hippo signaling pathways played important roles in hair follicle regeneration 80 and development of alopecia.…”
Section: Resultsmentioning
confidence: 99%
“… 76 Studies show that semaphorin-3a (Sema3a)-induced axonal growth cone collapse depends on HS3ST, indicating that activities of the semaphorin family rely on HS modifications. 77 , 78 , 79 TPGs of alopecia mainly cluster into two pathways termed the “Wnt signaling pathway” and the “Hippo signaling pathway” ( Figure 4 L). A previous study indicated that Wnt/β-catenin and Hippo signaling pathways played important roles in hair follicle regeneration 80 and development of alopecia.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, we found that Sema3A expression in the hippocampus was increased in a mouse model of PPD, which was associated with anxiety and depression-like symptoms. As Sema3A is an axon guidance molecule ( Perez et al, 2021 ) and the accumulation of Sema3A in the hippocampus can induce programmed cell death of neurons ( Good et al, 2004 ), we speculate that the upregulation of hippocampal Sema3A in PPD mice influences synaptic plasticity or neuronal activity to cause anxiety and depression-like behaviors.…”
Section: Discussionmentioning
confidence: 98%
“…Semaphorin 3A (Sema3A) is a secreted protein in the nervous system that is involved in axon guidance ( Perez et al, 2021 ), neuronal migration ( Chen et al, 2008 ), and synapse formation ( Tillo et al, 2012 ). Sema3A has been implicated in neuropsychiatric diseases such as schizophrenia ( Gilabert-Juan et al, 2015 ), Alzheimer’s disease (AD; Wang et al, 2021 ) and epilepsy ( Van Battum et al, 2015 ), and its accumulation in hippocampal neurons induces programmed cell death, which is shown to contribute to AD development ( Good et al, 2004 ).…”
Section: Introductionmentioning
confidence: 99%